CLIL-ing Your Coursebook - David A. Hill (Universidad de La Sabana, 2009)
This article suggests that CLIL is an important new approach to language teaching, at last grounding lesson content in something educational, rather than the endless trivia of many coursebooks for general English. However, the dearth of suitable materials available is noted, and the suggestion is that teachers create their own CLIL materials starting from suitable parts of their own current coursebook, rather than wait a few years for the ELT publishing market to respond to the need for new materials. It then exemplifies this approach with reference to a page from a course for 11-12 year olds written for the Bulgarian market, showing how materials can be built out from what is within the book.